Social Media and Political Participation in the 2023 General Election in Lagos State - Jenifer Olajumoke Oni; Idris Mohammed; Joy Collins-Dike; Muhammad Ridwan (Polit Journal Scientific Journal of Politics, 2024)
This study focuses on the use of social media and political participation in the 2023 general election in Lagos State. The study emanates from the idea that social media offers new platforms for communication, participation, and political engagement. This study examines the role of social media in shaping political participation during the 2023 general election in Lagos State, Nigeria. Through the quantitative analysis method, this research seeks to explore the extent to which social media influenced voter engagement, political discourse, and electoral outcomes in Lagos State. It objectives sought to: assess the factors informing social media use; and determine the effects of political use of social media. The study adopts Uses and Gratification as theoretical framework. Survey method was employed as a method of data collection through questionnaire. A sample of 364 residents of Iju Ishaga was used for the analysis. Based on the findings, residents of Iju Ishaga used social media because of easy access, availability and interactivity. The findings of the study revealed that social media plays a significant role in participatory politics among the residents of Iju Ishaga. The study discovered that residents of Iju Ishaga are quite active on social media particularly on WhatsApp. The platform is essential in both offline and online political activities, thus, enhancing political knowledge and increasing political participation and inclusion in Nigeria. The study also discovered that the residents with regular use express their political and policy preferences by engaging themselves and political actors directly through social media platforms. They are able to post their opinions and contribute to political discourses.